PENINGKATAN KETERAMPILAN MENGENALI PERILAKU ANAK TUNA LARAS MELALUI MODEL PEMUELAJ ARAN BEll.KEMAll - Masitoh, Siti (MAJALAH ILMIAH PEMBELAJARAN, 2008)
111e students were d{fficult to under.s:tand this lesson, e.\pecially to identifY child behaviour disorder. The research was aimed to imprcve their critical thinking with in identifY child behavior disorder. Because of //1u/ lecturer teaches this lesson must .'ook effort so students can irlenti/i1 child behaviour disorder with improved thinking sKill of students om/ dev<·lo1wd learning strategic of them, s1 1ch as organized learning stratex_v and metacognitive to chose learning camp model as altemative solution learning problem. The reseacher was designed as a classroom ac:t ionresearch with two cycles. This result research can give reco111111emlotion that learning camp model to improve learning quality, eSJJeciallv occ11ring impr<M'd critical thingking 1f students so they cm1 at'l'fl' teoritic about child behaviour dis01der to recognize and identifji child hehaviour disorder practically be in:errelated with child behavior edurntion I.